PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI KHUSUSNYA INTERNET PADA KELOMPOK TANI SARI GUNUNG TIGA DI DESA RUSA KENCANA KECAMATAN TOILI KABUPATEN BANGGAI (The Use Of Information and Communication Tecnology Especially The Internet In The Sari Gunung Tiga Farmer Group In The Village Of Rusa Kencana, Toili Sub-District, Banggai Regency) - Yunita Apriani Natalia; Vicky R. B. Moniaga; Grace A. J. Rumagit (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The objective of this research is to determine the use of information and communication technology (ICT), especially internet in the Sari Gunung Tiga farmer group, Rusa Kencana village, Toili Sub District, Banggai Regency. The research was carried out in Rusakencana village, Toili Sub District, Banggai Regency and over a period of 3 months, from December 2020 to February 2021. The data used in this study are primary data and secondary data. Primary data was obtained through direct interviews with farmer groups, using a list of questions that had been prepared. Secondary data were obtained from agencies related to this research, among others, literature or previous research. Sampling is purposive sampling where the sample is taken intentionally. The population taken is a farmer group with the sample taken 1 farmer group, namely the Sari Gunung Tiga farmer group consisting of 20 members/respondents. The research results showed that, the use of information and communication technology in farmer groups who use the internet 30% and the internet for the function of farmer groups, namely as a learning class, a vehicle for cooperation, and a production unit of 15% are classified as small.